O54 Child simulated patients: being ethically responsible. (5th November 2017) - Hamilton, C; Clarkson, G; Perry, J
Abstract : Background: The ASPiH Standards focus on faculty (safe learning environment) activity (patient perspective) and resources (variety of modalities). Considering these standards and the paucity of information regarding the ethical implications of engaging with child simulated patients (cSPs), ¹ our aim was to become standards compliant and ethically responsible when working alongside cSPs. Project Description: The principles of biomedical ethics; respect for autonomy, non-maleficence, beneficence and justice offer a broad consideration of medical ethics issues. These can legitimately be used in the context of cSPs. We created an adapted ethical framework (AdEF), underpinned by these principles. Information regarding the 'experience' of working with cSPs was gathered from local, national and international forums, then sifted into the AdEF. Ethical and practical implications of working with children are inextricably linked. A highly effective cyclical process of ethics v practicalities enabled us to categorise more succinctly. We tested the AdEF, adding and shifting the descriptors, whilst consulting with parents, teachers, ethics committees, organisations and current/former cSPs. Outcomes: The AdEF is a highly effective model which provides an oversight of working ethically with cSPs. Analysis of each principle has revealed the following exemplars of ethical responsibility: * Expert recruitment and ongoing suitability * Scenarios in conjunction with cSPs * Moulage involvement * Facilitator/cSP 'codes' for change in 'affect' * Heightened cSP awareness of health/safety issues * Confidence through advocacy * Informal debrief as important as formal debrief * Governance e.g., consent/personal details/information forms * Delegated responsible guardian(DBS) * Portfolio e.g., photos/certificate * Liaison with schools e.g., commendation /curriculum matching critical evaluation indicates a reduction of adverse events through considering the AdEF, however challenges persist, notably: coercion, assessment of maturity, role portrayal, training calibre, fluctuating abilities, feedback delivery and faculty responsibility. Conclusions: The ethics of working with cSPs is often questioned². Adherence to the AdEF and the ASPiH standards, with ongoing scrutiny of practicalities and governance, a safe ethical environment can be maintained. We believe that the benefit to the child, their family, their friends, to health care professionals and to society, should not be underestimated. As a separate study, we intend to gather information from cSPs who have now entered adulthood. The AdEF can be used across organisations to guide the ethical responsibility of those working with adult simulated patients (SPs), including other groups of SPs routinely engaged with, e.g., SPs with learning disabilities, SPs with English as a second language and SPs who are transgender. References: 1. Gamble A, Bearman M, Nestel D. A systematic review: Children & adolescents as simulated patients in health professional education. Advances in Simulation 2016;1(1):1. . Khoo EJ, Schremmer RD, Diekema DS, Lantos JD. Ethics rounds: Ethical concerns when minors act as standardised patients. Paediatrics2017;e20162795.